2013
DOI: 10.1136/bmjopen-2013-003056
|View full text |Cite
|
Sign up to set email alerts
|

Public views on the donation and use of human biological samples in biomedical research: a mixed methods study

Abstract: ObjectiveA mixed methods study exploring the UK general public's willingness to donate human biosamples (HBSs) for biomedical research.SettingCross-sectional focus groups followed by an online survey.ParticipantsTwelve focus groups (81 participants) selectively sampled to reflect a range of demographic groups; 1110 survey responders recruited through a stratified sampling method with quotas set on sex, age, geographical location, socioeconomic group and ethnicity.Main outcome measures(1) Identify participants’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
55
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 38 publications
9
55
1
Order By: Relevance
“…Our informants could grasp the response‐adaptive trial design and saw it as advantageous, particularly during a pandemic outbreak, but did not necessarily consider information about study design as a priority during an outbreak. Our findings confirm the general public's acceptance of donating excess material from routinely collected clinical samples for biomedical research provided safeguards are in place to protect against identification of the individuals and that the research was being performed primarily for patent benefit rather than to make a profit …”
Section: Discussionsupporting
confidence: 72%
“…Our informants could grasp the response‐adaptive trial design and saw it as advantageous, particularly during a pandemic outbreak, but did not necessarily consider information about study design as a priority during an outbreak. Our findings confirm the general public's acceptance of donating excess material from routinely collected clinical samples for biomedical research provided safeguards are in place to protect against identification of the individuals and that the research was being performed primarily for patent benefit rather than to make a profit …”
Section: Discussionsupporting
confidence: 72%
“…Some previous studies have identified several sociological characteristics and personal factors associated with the willingness to participate in the specimen donation and biobank researches. In general, different gender, age, nationality, marriage, education background, donation history, family disease and the knowledge of biospecimen donation have been proved can influence public's willingness in specimen donation [6,[24][25][26]. Also, researches have reported that people with higher education background may hold more positive attitudes toward donation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Many supported the sharing of biosamples with other organisations after use, but often with conditions about the nature of the organisation and the types of uses to which samples will be put, and with concerns about anonymity and misuse. Commercial organisations were generally viewed negatively, while advancements in medical science were viewed favourably, echoing existing research [ 10 , 24 , 33 ]. Lewis and colleagues [ 8 ] identified similar aversion to commercial organisations, as well as some misgivings about animal research and research conducted outside of the UK.…”
Section: Discussionmentioning
confidence: 99%
“…Ownership of donated biosamples is another issue raised by research using biosamples [ 7 , 24 , 25 ]. While the MRC advise that donations should be part of a ‘gift relationship’ that reduces ‘uncertainty over ownership’ [ 26 ], Dixon-Woods and colleagues [ 27 ] argue that ethical policy based on Titmuss’ model of altruism without expectations of reciprocity [ 5 ], is unsuitable for modern medical research, in which distinctions between not-for-profit and commercial research are not always distinct.…”
Section: Introductionmentioning
confidence: 99%